Tuesday

September 23, 2014

September 23, 2014

Posted by **Kris** on Thursday, July 18, 2013 at 6:30am.

- math -
**Steve**, Thursday, July 18, 2013 at 10:25amlg y = lg .1 + lg (1000^x) = lg .1 + (lg 1000)x = -1 + 3x

**Answer this Question**

**Related Questions**

Calculus: Determine the constants from function - The function h(x) = x^3 + bx^2...

Calculus - The population (in thousands) of the Tzitzit bird is well described ...

math - Express 2 lg 3√x - lg 4/3x^2 + log(100)4x^3 in the form a lg x + lg...

Math - Let f(x)=2x^2+3px-2q and g(x)=x^2+q,where p and q are constants.It is ...

Mathematics - How do i solve the pair of simultaneous equations y=x^2-3x-12 and ...

Math - Continuity - Determine the constants a and b so that the function f is ...

CHEMISTRY HELP! - Consider the following reactions and their equilibrium ...

Maths - Transform the following relationships/funtions into linear form and ...

Physics - A bowling ball rolls without slipping up a ramp that slopes upward at ...

Math - Let f(x)=ax^5+bx^3+cx+9, where a,b, and c are constants. If f(6)=17, ...